Agroforestry as a Tool for Sustainable Rural Development: A Mini-Review - Haider, Samsam (PSM Biological Research, 2019)
Agro-forestry in developing countries must undertake significant yield improvement to meet the combined challenges of population growth and food for sustainable livelihood. The world population growth rate is increasing but the situation is at an alarming rate in developing countries. The pressure is increasing on the world’s natural resources which arise from population growth that resulted in unsustainable use of natural resources, depletion of forest cover due to an increased hunger for forest and non-forest products. These negative effects on developing countries need fundamental attention. This paper reviews the sustainable magnitude of agro-forestry and discusses the various agroforestry practices that are the pillars of development for enhancing the capacity of rural dwellers. Agro-forestry refers to the combination of practicing agriculture and forestry on the same unit of land. Agro-forestry is a means of halting the vicious circle of deforestation, soil erosion and other environmental problems facing the country. Agro-forestry is performed with innumerable benefits that produced a social, ecological and environmental benefit on a large scale and also increases the value of land with much-needed profit and food security for a healthy and productive life of rural dwellers. Agro-forestry practices provide food, shelter, wood, cash and a variety of other products and protective benefits that are ecologically strong, economically efficient and socially sustainable.